The Twin Study of Negative Valence Emotional Constructs. (26th July 2016) - Carney, Dever M.; Moroney, Elizabeth; Machlin, Laura; Hahn, Shannon; Savage, Jeanne E.; Lee, Minyoung; Towbin, Kenneth A.; Brotman, Melissa A.; Pine, Daniel S.; Leibenluft, Ellen; Roberson-Nay, Roxann; Hettema, John M.
Abstract : The Twin Study of Negative Valence Emotional Constructs is a multi-site study designed to examine the relationship between a broad selection of potential measures designed to assess putative endophenotypes for negative valence systems (NVS) and early symptoms of internalizing disorders (IDs). In this article, we describe the sample characteristics, data collection protocols, and measures used. Pre-adolescent Caucasian twin pairs were recruited through the Mid-Atlantic Twin Registry; data collection began in February of 2013. Enrolled twins completed various dimensional self-report measures along with cognitive, emotional, and psychophysiological tasks designed to assess NVS function. Parents also completed surveys about their twins and themselves. In addition, a subset of the twins also participated in a neuroimaging protocols. Data collection is in the final stages, and preliminary analyses are underway. The findings will potentially expand our understanding of the mechanisms by which genetic and environmental factors contribute to individual differences in NVS phenotypes and provide new insights into underlying risk factors for IDs.